Atividade antioxidante, antibacteriana e anti-inflamatória do extrato metanólico e frações da alga parda Spatoglossum schroederi - Quesado Júnior, Sérvio (2012)
Methanol extract (MET) and hexane (HEX) and chloroform (CLR) fractions of brown seaweed Spatoglossum schroederi were evaluated for antioxidant, antibacterial and anti-inflammatory activities. Antioxidant activity was performed by total antioxidant capacity, reducing power, DPPH radical scavenging activity and ferrous ion chelating assay, which results were correlated with total phenol and flavonoid contents. The samples showed low total phenol content (6.84 to 14.10 mg GAE/g) and high total flavonoid content (215.39 to 279.63 mg QE/g). They also showed good antioxidant activity for total antioxidant capacity (120 mg ascorbic acid equivalent antioxidant capacity / g) and reducing activity (0.414 to HEX, the highest value), which results were strongly associated with their total flavonoid content, R2>0.9. For DPPH radical scavenging activity, fractions showed pro-oxidant action to a concentration above 1.5 mg/mL. No activity was detected for ferrous ion chelating assay. Antibacterial activity was tested by agar diffusion method against two Gram-positive and three Gram-negative bacteria. None of the samples at the concentrations tested (50 and 100 mg/mL) showed bactericidal effect. Anti-inflammatory activity was evaluated by paw edema induced by carrageenan and dextran, leukocyte migration, myeloperoxidase activity and cytokine measurements. All samples showed good anti-inflammatory activity in such tests. In paw edema, anti-inflammatory activity inhibited at the peak edema, with better results for HEX (near 100%) for carrageenan, and for CLR (79%) and HEX (77%) for dextran. HEX also showed the best results in inhibition of leukocyte migration, both total (71%) and differential (74%). CLR showed the best value in myeloperoxidase activity (87%). The samples showed a very close reduction in IL-1β, nearby 43%. MET did not affect production of IL-10, but HEX and CLR induced production of IL-10, HEX having the best value (80%). Such results can be explained by flavonoids high content. S. schroederi, especially hexane fraction, has potential for pharmacologic and antioxidant uses. However, further studies are needed to elucidate the metabolic pathways involved and to isolate the bioactive molecules.